2020
DOI: 10.1186/s12889-020-8274-z
|View full text |Cite
|
Sign up to set email alerts
|

Explaining variance in health literacy among people with type 2 diabetes: the association between health literacy and health behaviour and empowerment

Abstract: Background: To reflect the health literacy (HL) skills needed for managing type 2 diabetes (T2DM) in everyday life, HL in people with T2DM should be measured from a broader perspective than basic skills, such as proficiency in reading and writing. The HLS-Q12, based on the European Health Literacy Survey Questionnaire (HLS-EU-Q47), assesses four cognitive domains across three health domains. International studies on people with T2DM show inconsistent results regarding the association between HL and general hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 50 publications
2
19
1
7
Order By: Relevance
“…Having su cient HL might be more important than ever before because people are expected to participate in health decisions and to take responsibility for their own health despite more complicated health problems and the need to navigate a more complex health system [21][22][23] . In this survey, only 4.15% (31.95 ± 11.81 points on average) of the residents in poor counties achieved su cient health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Having su cient HL might be more important than ever before because people are expected to participate in health decisions and to take responsibility for their own health despite more complicated health problems and the need to navigate a more complex health system [21][22][23] . In this survey, only 4.15% (31.95 ± 11.81 points on average) of the residents in poor counties achieved su cient health literacy.…”
Section: Discussionmentioning
confidence: 99%
“…Todos os 19 estudos apresentados nesta revisão de escopo foram publicados entre o ano de 2016 (Santos & Portela, 2016;Punte-Maestu et al 2016;Wannasirikul, Termsirikulchai, Sujirarat, Benjakul & Tanasugarn, 2016;Cox et al 2016) e o ano de 2020 (Souza, Farfel, Jaluul, Queiroz & Nery, 2020;Do et al 2020;Finbraten et al 2020). Dos trabalhos selecionados, segundo seus tipos de estudo, foram identificados nove coortes (Punte-Maestu et al 2016;Fabbri et al 2018;León-González et al 2017;Yu, Wilson, Han et al 2017;Shi et al 2017;Lamar et al 2018;Cox et al 2016;Wilson, Yu James, Bennett & Boyle, 2017;Yu, Wilson, Schneider, Bennett & Boyle, 2017), um ecológico (Santos & Portella, 2016) e nove estudos transversais (Costa, Costa, Nakano, Apolinário & Santana, 2019;Souza et al 2020;Como, 2018 González, Gonzáles-Pérez, Gestal-Otero & Díaz-Grávalos, 2018;Murtaugh et al 2017;Do et al, 2020;Finbraten et al 2020;Liu, Xue, Xue & Hou, 2018;Wannasirikul et al 2016). Todos os trabalhos tinham como objetivo identificar a relação do letramento em saúde com algum desfecho clínico investigado, conforme informações apresentadas no Quadro 1.…”
Section: Fonte: Autores (2021)unclassified
“…Communicative health literacy determines an advanced level of individuals' literacy skills, allowing people to extract information and meaning derived from the various communication channels by putting them into practice to change the conditions. Critical health literacy refers to highly advanced skills, which help analyzing information to use knowledge to gain more control over events of individuals' lives and day-to-day circumstances [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…They have emphasized personal responsibility to maintain and promote health literacy and self-management of chronic diseases and diabetes type 2,4 and 5 [6,7]. A survey conducted in the US showed that more than 33% of individuals did not have appropriate health literacy [5]. Earlier study results indicated that 31% of the Iranian diabetes patients had adequate health literacy [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation